Evaluasi Sistem Pengendalian Intern Terhadap Efektivitas Pemberian Kredit - Hasibuan, David; Pamungkas, Bambang; Monang, Gatot Luhut (Institut Bisnis dan Informatika Kesatuan, 2015)
Bank as a financial institution in Indonesia has an important role in improving standards of living. For that one effort to improve people's lives is the provision of credit to the public. In the course of the loan, the bank is obliged to apply the precautionary principle to avoid an issue. The purpose of this study is to determine the intemal control system at the Bogor branch of Bank BTN and the effectiveness of lending undertaken by the Bank. As well as how big the role of a credit effective internal control systems in Bank BTN Branch Bogor. Based on the research data obtained, it is blown that the intemal control conducted by the Bogor branch of Bank BTN is sufficient to support the loan granted by the bank. The results show that the intemal control plays an important role in the effectiveness of the loan made by the bank It can be seen from all components of internal control that has been executed by the bank. Among the separation of duties, authorization is performed by the right people, and document storage is assured, and risk assessment is always made by the bank. Of the components of intemal control has an impact on its effective lending procedures performed by the bank, so they can minimize the risk that a bank will occur in the future. Keywords : Internal Control, Lending of Credit